The Role of the Student in the Literary Translation Classroom: A Pedagogical Approach Towards a New Learning Perspective - FernÃ¡ndez-Alonso, Alba (European Scientific Journal, ESJ, 2022)
Despite the full involvement of students in their learning process, the translation classroom still faces challenges associated with the implementation of traditional teaching schemes. Ideally, students should be invited to reflect and exchange perspectives that help them internalize the different stages that take place during the stages of the translation process. Among these, intuition and deduction come into play and lead to the creation of a habit through induction that allows the students to face the translation problems arising from the text in a satisfactory manner, thus contributing to the development of their translation competence. This proposal is designed within a framework of active learning in which students stop being spectators in the classroom to become the protagonist of their own learning process by being continuously exposed to situations that demand higher-order intellectual operations. The methodology employed in class will take place in three different stages: comprehension of the source text, interlingual translation and an individual assessment of the target text. This three-fold learning strategy favors an active attitude in students and compels them to perform activities effectively. We believe that this proposal will help us achieve our main objective, which is to help our students delve into the complexities and problems associated with the field of literary translation while fostering the foundations of collaborative learning in the classroom.